GEOMETRIC COMPLEXITY ANALYSIS IN AN INTEGRATIVE TECHNOLOGY EVALUATION MODEL (ITEM) FOR SELECTIVE LASER MELTING (SLM)# - Merkt, S.; Hinke, C.; Schleifenbaum, H.; Voswinckel, H. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Selective laser melting (SLM) is becoming an economically viable choice for manufacturing complex serial parts. This paper focuses on a geometric complexity analysis as part of the integrative technology evaluation model (ITEM) presented here. In contrast to conventional evaluation methodologies, the ITEM considers interactions between product and process innovations generated by SLM. The evaluation of manufacturing processes that compete with SLM is the main goal of ITEM. The paper includes a complexity analysis of a test part from Festo AG. The paper closes with a discussion of how the expanded design freedom of SLM can be used to improve company operations, and how the complexity analysis presented here can be seen as a starting point for feature-based complexity analysis.. AFRIKAANSE OPSOMMING: Selektiewe lasersmelting word geleidelik